Challenges to "a Most Dangerous Doctrine" or a "Fantastic Theory" of Volitional Insanity - Bastani, Amir; Gavaghan, Colin (Victoria University of Wellington Law Review, 2016)
In theory, an insanity defence can take two forms: the cognitive form (C-insanity) and the volitional form (V-insanity). The defence of C-insanity recognises that a disordered state of mind can make the ability to understand the nature of an action impossible. On the other hand, V-insanity is recognised in some common law jurisdictions, such as all jurisdictions in Australia except for Victoria and New South Wales, and is a full defence. It recognises that a disordered state of mind can make the exercise of self-control impossible. However, that disordered state of mind does not necessarily affect the understanding of the nature of the act impossible.